A new species of Dialeurolobus (Hemiptera: Aleyrodidae) from Protea nitida in South Africa - Millar, I. M.; Dooley, J. W. (Zootaxa, 2013)
Dialeurolobus proteae sp. nov. is described from Protea nitida (Proteaceae) in South Africa, and from specimens intercepted on protea plants imported into the U.S.A. from South Africa. Its affinities to the other species of Dialeurolobus are discussed, and a diagnostic key is provided to identify the species of this genus.